2014
DOI: 10.1063/1.4869515
|View full text |Cite
|
Sign up to set email alerts
|

Communication: Different behavior of Young's modulus and fracture strength of CeO2: Density functional theory calculations

Abstract: In this Communication, we use density functional theory (DFT) to examine the fracture properties of ceria (CeO 2 ), which is a promising electrolyte material for lowering the working temperature of solid oxide fuel cells. We estimate the stress-strain curve by fitting the energy density calculated by DFT. The calculated Young's modulus of 221.8 GPa is of the same order as the experimental value, whereas the fracture strength of 22.7 GPa is two orders of magnitude larger than the experimental value. Next, we co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…Sakanoi and co-workers used density functional theory to calculate the Youngs modulus (221.8 GPa) and fracture strength (22.7 GPa) of CeO 2 . 16 This compares with 175 GPa (Youngs modulus) and 0.25 GPa (fracture strength) measured experimentally. They attributed the difference in fracture strength to the presence of cracks that were not included in the structural model; combined with Griffith theory, which modifies the ideal fracture strength as a function of crack length (taken as 20 mm), they predicted that the fracture strength reduces to 0.5 GPa -in close accord with experiment.…”
Section: Poissons Ratiossupporting
confidence: 50%
See 1 more Smart Citation
“…Sakanoi and co-workers used density functional theory to calculate the Youngs modulus (221.8 GPa) and fracture strength (22.7 GPa) of CeO 2 . 16 This compares with 175 GPa (Youngs modulus) and 0.25 GPa (fracture strength) measured experimentally. They attributed the difference in fracture strength to the presence of cracks that were not included in the structural model; combined with Griffith theory, which modifies the ideal fracture strength as a function of crack length (taken as 20 mm), they predicted that the fracture strength reduces to 0.5 GPa -in close accord with experiment.…”
Section: Poissons Ratiossupporting
confidence: 50%
“…Experimentally measure values 15 are also reported in Table 1 together with density functional theory calculations on fully dense ceria. 16 Stress-strain curves, for the hexagonal pore system without dislocation under uniaxial compression, Fig. 9, reveal near linear elastic regions followed by plastic deformation and collapse of the nanoarchitecture.…”
Section: Mechanical Propertiesmentioning
confidence: 95%
“…[180,288] Fracture strength and toughness largely depend on flaws, cracks, and voids; thus, variability in solid-electrolyte manufacturing can have a catastrophic effect. [275,289,70,76,179,257,[280][281][282][283][284][285][286][287] Polycrystalline ceramic oxides typically exhibit hardness and fracture toughness in the range of 0.8-26 GPa and ≈1.5-15 MPa m 1/2 , respectively. [276,290,291] The garnet LLZO, perovskite LLTO, and NASICON-type oxide LATP are stiff (E ≈ 100-200 GPa) with hardness values of 6.8-9.9 GPa (depending on the grain size and porosity) with a single-crystal hardness of ≈9.1, [178,179] ≈9.5, [268,292] and 7.1 GPa, [268] respectively, and an average fracture toughness of ≈1.25, ≈0.92, and ≈1.1 MPa m 1/2 , respectively (relative density >97%) (Figure 3).…”
Section: Oxidesmentioning
confidence: 99%
“…[180] Hardness is a global property depending not only on the crystal structure and bonding [293] but also on the microstructure, i.e., the porosity, grain size, defects, flaws, cracks, voids, grain boundaries, inhomogeneity, and secondary phases (as well as probe size). [178,257,275,289] Cubic Ta-doped LLZO (relative density 92%-98%) exhibited large scatter in the single-crystal hardness, ranging from ≈9-12 GPa (the large scatter was related to surface roughness); however, once considering microstructure features, the effective hardness was unified at ≈5-6 GPa. [119] Recently, the microscopic/local hardness of LLZO was assessed using the micro-pillar indentation splitting method and was determined to be ≈8.5 GPa (with a fracture toughness of 0.99 MPa m 1/2 ).…”
Section: Oxidesmentioning
confidence: 99%
“…Studies have shown [19][20][21][22] that the roof of the working face tends to fracture structure, which is closely related to the microstructure of the material and the state of the section coal pillar. The method of simulating experiments using physical similar materials can well restore the roof fracture structure of the working face.…”
Section: Model Of Similar Designmentioning
confidence: 99%